In Situ Side-to-Side Pericallosal-Pericallosal Artery and Callosomarginal-Callosomarginal Artery Bypasses for Complex Distal Anterior Cerebral Artery Aneurysms: A Technical Note. Issue 5 (29th July 2020) - Acerbi, Francesco; Vetrano, Ignazio G; Falco, Jacopo; Gioppo, Andrea; Ciuffi, Andrea; Ziliani, Vanessa; Schiariti, Marco; Broggi, Morgan; Faragò, Giuseppe; Ferroli, Paolo
Abstract: BACKGROUND: Despite surgical and endovascular technical improvements over the last decades, the treatment of complex aneurysms of the distal anterior cerebral artery (ACA) is very challenging for both vascular neurosurgeons and interventional neuroradiologists. Furthermore, the interpersonal anatomic variability requires, most of the time, a tailored planning. OBJECTIVE: To describe a novel technique of bypasses in the territory of ACA to protect the brain territory distal to the aneurysm. METHODS: A 53-yr-old male with a large complex fusiform aneurysm of the left distal A2 segment of the ACA, involving the origin of the callosomarginal and pericallosal arteries, was judged not suitable for a single procedure (endovascular or neurosurgical). Two side-to-side bypasses were performed in a single surgery to connect the pericallosal and callosomarginal arteries of both sides, distally to the aneurysm. Subsequently, an endovascular embolization of the aneurysm was achieved with coils. RESULTS: The patency of the microanastomoses, performed in the anterior interhemispheric fissure, was positively evaluated intraoperatively with indocyanine green and fluorescein videoangiography. The aneurysm sac, together with proximal A2 segment, was completely occluded with platinum coils. At the last follow-up, computed tomography angiography confirmed the patency of both bypasses, without any sign of aneurysm recanalization. The patients never complained of any focal neurological deficits or worsening of clinical status. CONCLUSION: We present an elegant and innovative solution to completely protect the distal ACA territory in cases of complex aneurysm involving the origin of both callosomarginal and pericallosal arteries.